Balancing old and new, delicately - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The architects of the large meeting room at the CTA headquarters got it right with the design of its castle-like walls with high slit-like windows; the light cascades in, sometimes blindingly, a constant reminder of the world outside. Small wonder...